Intermodal Priming of Cognitive Conflict? A Failed Replication of Mager et al. (2009) - Wiswede, Daniel; Rüsseler, Jascha (Frontiers in Human Neuroscience, 2021)
The present study was conducted to verify a promising experimental setup from another research group which demonstrated an inversed Stroop-effect (much faster responses for incongruent relative to congruent Stroop trials) following a mismatching tone. In the matching condition, which was an almost exact replication of the original study, participants were required to indicate whether word colour and word meaning were matching, whereas in the response conflict condition, instruction was the same as in a classical Stroop task and required the participants to respond to the word colour. As in the original study, each trial was preceded by a sine tone which was deviant in pitch in 20% of the trials. Results: The main result was that the Stroop effect was not inversed after deviant tones, neither under the matching task instruction nor under the response conflict task instruction. The Stroop effect was unaffected by the previous “conceptual mismatch”. Conclusion: The current study failed to replicate the astonishing concept of “conflict priming” reported in previous work and does not open the doors for a new window on sequences of conflicts. Nevertheless, the failed replication is valuable for future research, since it demonstrated that “Conflict Priming” as a facilitation of processing of conflict trials following deviant tones, does not existis not an confirmed finding.